2014
DOI: 10.1007/s00246-014-1042-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Assessment in Children Followed in a Cardiomyopathy Clinic

Abstract: As our ability to diagnosis cardiomyopathy matures and genetic testing becomes more widespread, there has been an increase in the number of children followed for cardiomyopathy. The purpose of this study was to compare health-related quality of life (HRQoL) between children with cardiomyopathy and healthy controls and with children seen in clinic who are at risk for the development of cardiomyopathy. Patient and parent-proxy perspectives were obtained using the Pediatric Quality of Life Inventory (PedsQL(TM)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…It must be noted that even in adults living with heart failure without symptoms (Stage B), health-related quality of life is noted to be impaired. 21 Freiss et al 9 recently reported similar findings with noted impaired health-related quality of life in children with a family history of cardiomyopathy (Stage A). Thus, presence of symptoms in patients with heart failure is not required to have detrimental effects on health-related quality of life.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It must be noted that even in adults living with heart failure without symptoms (Stage B), health-related quality of life is noted to be impaired. 21 Freiss et al 9 recently reported similar findings with noted impaired health-related quality of life in children with a family history of cardiomyopathy (Stage A). Thus, presence of symptoms in patients with heart failure is not required to have detrimental effects on health-related quality of life.…”
Section: Discussionsupporting
confidence: 52%
“…At present, little data exist with regard to healthrelated quality of life in children with heart failure. 8,9 The purpose of this study was to compare the selfreported and parent proxy-reported health-related quality of life in children with heart failure with that of the healthy paediatric population, children with other chronic conditions, and children with cardiovascular disease. In addition, we report potential modifiers of health-related quality of life in the paediatric heart failure population, including ejection fraction, physical activity restriction, presence of pacemaker or implantable cardioverter-defibrillator, and American Heart Association stage of heart failure.…”
mentioning
confidence: 99%
“…Although there are prospective studies of the health-related quality of life (HRQOL) of children with congenital heart disease 6,7 and noncardiac conditions, 810 few have studied children with cardiomyopathy. 11,12 Such information may be useful for counseling, identifying families in need of special services, and in the planning of clinical management strategies.…”
mentioning
confidence: 99%
“…It involves life-long medications, at times longterm infusions like milrinone administered through peripherally-inserted central catheters (with their own risks including catheter malfunctions and infectious complications), close monitoring and regulation of nutrition and fluid intake, possible need for nutrition repletion strategies such as gastric tubes due to the failure to thrive associated with HF, and the ever-looming possibility of worsening HF precipitating the need for heart transplantation or mechanical circulatory support. Children with HF are reported to have worse quality of life than their healthy peers as well as a worse quality of life when compared to children who have received a heart transplant [16,17]. While there are no reports on the routine utilization of PPC teams in the care of pediatric patients with HF, it may be beneficial to consider early PPC engagement if a child appears to be heading towards transplant or VAD.…”
Section: Heart Failurementioning
confidence: 99%